Cross-cultural competence and professional formation of music educators - Saltanat Taspayeva; Laura Kakimova; Narman Peruza; Roza Sydykova (Institute of Advanced Engineering and Science, 2026)
Globalization increased cultural diversity in music education. This required music educators to develop cross-cultural competence (CCC). This study evaluated the impact of CCC on the professional development (PD) of music educators. The research employs a mixed-methods approach, combining surveys with qualitative interviews conducted among music educators from different cultural backgrounds. The study used stratified random sampling to obtain representative participants with primary, secondary, and tertiary music education. The novelty of this study lies in the application of a mixed-methods design within the under-researched context of music education in Kazakhstan. The research included 200 music educators spanning different educational levels for the quantitative phase and 20 music educators for participant observation and interview for the qualitative stage. The results of the study indicated that educators with strong intercultural competence (ICC) may be better prepared to adapt teaching methods with students from different cultural backgrounds. Such educators also had enhanced interpretive abilities across different musical genres. Therefore, when educators have intercultural skills, they become more inclusive and innovative. Additionally, PD initiatives for music educators should include models of ICC to develop pedagogical effectiveness and expand musical literacy.